Potential of Tri Eka Buana Village as an Arak Tourism Village through the Creative Tourism Concept in Karangasem Regency - Wisudawati, Ni Nyoman Sri; Sudharma, Kadek Januarsa Adi (Graduate School, Universitas Brawijaya, 2023)
This study aims to describe the potential of Tri Eka Buana village as a tourist destination producing Arak through the application of creative tourism in terms of tourist activities or a place that produces Arak. The research uses qualitative study and field research to find the potential of Tri Eka Buana as a creative tourist destination. We identified the potential of Tri Eka Buana village and then explored the contribution of the local community to develop the village as a creative tourism destination. We also assessed the perception of the community leaders and community who play role in the development of tourism activities in Tri Eka Buana village. In the first stage for the result, the potential of Tri Eka Buana village is very supportive in developing as a creative tourism destination with the characteristic of Arak village. It is supported by the natural and socio-cultural environment that is still well maintained in the globalization era. The second stage of the result is about the contribution of the local community to support Tri Eka Buana village as a creative tourism destination obtained through in-depth interviews with the village head, Arak farmers, and owner of Arak production. These investigations identify the role of all levels of society in developing the Tri Eka Buana villages as creative tourism destinations. Another result implied that not only the role of local communities but also the role of the local government is needed for development and sustainability. Keywords: Arak (authentic local beverage), Creative tourism, Tourism village.